The rhizome perspective: a case study on community radio in Yogyakarta, Indonesia - Yustitia, Senja; Ashrianto, Panji Dwi (Jurnal Studi Komunikasi, 2026)
The condition of community radio is always linked to its ability as a medium to provide diversity of information amid a homogeneous media industry dominated by conglomerates. On the other hand, they are very likely to experience powerlessness, mainly due to the narrow dichotomy formalised by regulations. This study focused on four radio stations in Yogyakarta: Saka FM, BBM FM, Swaka FM, and Angkringan FM. This study examined the dynamics of community radio in managing community issues and how it can remain relevant to its communities. This qualitative research used a collective case study method. Data were collected through in-depth interviews with four community radio managers, broadcasters and experts, as well as direct observation at each radio station. The rhizome perspective was used to analyse the findings. The study concluded that community radio stations have stagnated in capturing the reality of their communities, especially socio-political issues. Secondly, the relevance of community radio stations to their communities is not based on their ability to address community issues, but rather on their role as entertainment media. These results indicate that it is difficult for radio stations to function as rhizomes as catalysts and to build interconnections.